Ayurvedic Management of Endometriosis w.s.r. to Vatiki Yoni Vyapada (AYUSHDHARA, 2024)
Endometriosis is a chronic, often painful condition in which tissue similar to the lining of the uterus grows outside the uterine cavity. Affecting approximately 10% of women of reproductive age, endometriosis can lead to severe pelvic pain, infertility, and other systemic symptoms. Despite its prevalence, the condition remains under-diagnosed and poorly understood, largely due to the complexity of its symptoms and variability in individual presentations. The treatment involves hormonal therapy and surgical interventions, but these may not always solve the underlying issue or may have significant side effects. This article explores Ayurvedic management of endometriosis by adopting the treatment principles of Vataja yonivyapada due to similarities of symptoms. A holistic approach is used by focusing on Vatanulomana by Shamana chikitsa and Shodhana and Sthanika chikitsa in the form of Nabhi purana with Eranda taila and Mruttika alepa. This is a case report of a 34 year old unmarried female patient suffering from endometriosis and having complaint of severe pain during menses. She was totally dependent on analgesics injections and oral painkiller during her menses since 2 years. The objective of present treatment included management of the symptoms by Ayurvedic intervention by formation of Shudha artava dhatu and balancing the Gati of Vata dosha and also improvement of the quality of life which was hampered during menses. After the treatment her dependency on the painkillers was gradually reduced.